Apoptosis of Rattus novergicus gingival fibroblasts caused by silver nano-particles gel exposure - Kharinna Widowati; Titiek Berniyanti; Retno Pudji Rahayu (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: The use of silver nanoparticle are growing, especially in medical science. It’s used in many concentration. In dentistry, it’s used to decrease halitosis, periodontal diseases, and wound healing. It can affect the viability of the cells, give bad effects to the human’s health and environment if used in a long duration and in certain concentration. Purpose: The purpose of this study was to learn the apoptosis of gingival fibroblasts in Rattus novergicus which is exposed with 15 µg/ml silver nano-particle gel by the expression of caspase-3. Method: This study used 9 male wistar rats and were divided into 3 groups. Sample in group A were cut (hurt) in the oral gingiva and exposed to Ag-Np gel 15 µg/ml for 3 days. After 3 days, they were sacrificed and cut the gingival fibroblasts off 3x4 cm size with scalpel. Samples in group B were cut in the oral gingiva and exposed to Ag-Np Gel 15 µg/ml for 5 days. After 5 days they were sacrificed and the gingival fibroblasts off 3 x 4 cm with a scalpel. Samples in group C were cut in the oral gingiva and exposed to none for 3 days then cut the gingival fibroblasts off 3 x 4 cm size with scalpel. The expressions of caspase-3 in the apoptotic and wound healing process were analyzed by Immunohistochemical test. This data was analyzed by using the t-test method. Result: Mean expression numbers of caspase-3 in the group A=5.67; group B=11.33; and group C (control)=18.67. T-test sign.number of group A and C=0.009; group B & C=0.000. Conclusion: The exposure of 15 µg/ml silver gel nanoparticle to gingival fibroblasts of Rattus novergicus reduces the expressions of caspase-3 in the day-3 and day-5 post exposure. The amounts of cell death through the apoptotic pathway which were analyzed by the expressions of caspase-3 will decrease too.